The effect of opioids on gastrointestinal function in the ICU - Yun Yan; Yu Chen; Xijing Zhang (Critical Care, 2021)
Abstract Gastrointestinal (GI) dysfunction is common in the critical care setting and is highly associated with clinical outcomes. Opioids increase the risk for GI dysfunction and are frequently prescribed to reduce pain in critically ill patients. However, the role of opioids in GI function remains uncertain in the ICU. This review aims to describe the effect of opioids on GI motility, their potential risk of increasing infection and the treatment of GI dysmotility with opioid antagonists in the ICU setting.